Interactive english reading tutor and vocabulary learning with voice recognition for children / Zulkifli Halim - Halim, Zulkifli (2010)
In Malaysian educational context, English Language is served as second language. It means English Language is also the important language that should be learned by the students starting from lower levels of schools such as lower primary school. However the problems exist when the children learn how to read a book without understanding the vocabulary and error in the pronunciation. Without knowing the vocabulary, reading alone will not help in understanding the reading materials such as a book. The objectives of this research are to design and to develop computer-based learning application using voice recognition in interactive way, to apply the active learning as learning approaches and test the functionality and usability of the application. The application is a supplement material for helping the children to improve their pronunciation and also their vocabulary on the English learning. This application will give a lot benefit to the children and educational field.